The Urgency of Screening for Thalassemia Carriers in Indonesia: Policy Analysis - Setiyowati, Erni; Rustina, Yeni; Allenidekania, Allenidekania (Utan Kayu Publishing, 2025)
Thalassemia is a hereditary blood disorder that, while incurable, is entirely preventable through early detection. In Indonesia, an estimated 6–10% of the population carries the thalassemia gene but screening is not a nationwide mandatory. Existing initiatives remain fragmented across regions and target only specific groups, such as prospective brides and grooms in Jakarta or pilot programs in Bekasi Regency. Lack of early screening leads to the birth of thousands of children with thalassemia major, requiring lifelong transfusions and iron chelation therapy that costs the government IDR 800 billion per year. To achieve long-term sustainability, Indonesia must shift from curative to preventive strategies by integrating genetic screening into the national health insurance and reproductive health systems. Policy Ask: Develop a joint regulation between the Minister of Health and the Minister of Religious Affairs, or Minister of Health Regulation (Permenkes), mandating premarital and school-based thalassemia screening as part of national health and marriage registration programs.